Investigating the Influence of Radiation Pressure on the Stability of Lagrangian Points in Celestial Mechanics - Shehu Adamu Aliyu; Habujika Abdulhadi Ismail (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Lagrangian points represent critical equilibrium configurations in celestial mechanics where gravitational and centrifugal forces balance, enabling small bodies to maintain relative positions with respect to two primary masses. This study investigates the location and stability of these points under the influence of radiative forces, with a particular focus on the role of radiation pressure in modifying gravitational equilibrium. Using a mathematical modeling approach, the research derives expressions for the collinear and triangular Lagrangian points and examines how radiation pressure affects their equilibrium configurations. The analysis shows that the positions of the collinear points shift as a function of the radiation parameter, while the stability characteristics of the triangular points are governed by the mass ratio of the system. These findings refine the theoretical understanding of Lagrangian dynamics in radiating systems and highlight the sensitivity of equilibrium configurations to radiative effects. The study concludes that incorporating radiation pressure is essential for accurately characterizing gravitational equilibrium in realistic astrophysical and space mission scenarios, thereby providing a more robust foundation for celestial navigation, satellite deployment, and space mission design, and contributing to a deeper understanding of orbital mechanics relevant to future space exploration missions.